Navigating the intersection: How antitrust law can facilitate fair standard essential patent licensing in China - Zhang, Yurong; Duan, Haiyang; Yang, Wei (Computer law & security review, 2025)
The integration of high-quality communication patents into technical standards has intensified competition and raised antitrust concerns in Standard Essential Patent (SEP) licensing. This paper examines China’s antitrust regulation of SEP licensing amid rapid market development and increasing alignment with international practices. Since entering the world stage, China has gone through an initial exploration phase (1992–2012), framework construction phase (2013–2019), and now the rules refinement phase (2020–). The antitrust enforcement rules regulating SEP licensing have become relatively clear. In particular, on November 8, 2024, the Anti-monopoly Guidelines for Standard Essential Patents issued by China’s State Administration for Market Regulation further refined the antitrust enforcement rules in the SEP licensing field. However, China’s antitrust regulation of SEP licensing faces significant challenges despite recent regulatory developments. This paper examines three critical issues: determining market dominance of SEP holders, assessing monopolistic behavior in injunctive relief requests, and establishing benchmarks for excessive or discriminatory pricing. Drawing from US and Europe enforcement experiences while considering China’s context, this study advocates for Chinese enforcement agencies to: (1) prioritize effect-based analysis when establishing SEP holders’ market dominance by examining standard irreplaceability and patent essentiality; (2) refine the criteria for determining whether rights holders have demonstrated clear misconduct when assessing the antitrust implications of injunctive relief requests, and consider these alongside other contextual factors; (3) maintain a clear distinction between excessive pricing and discriminatory pricing when assessing potential FRAND violations. Regarding excessive pricing allegations, antitrust intervention should proceed with caution on a case-by-case basis, integrating multiple factors to determine whether royalty rates significantly and persistently exceed benchmark rates. For discriminatory pricing concerns, authorities must evaluate whether pricing differentials in comparable SEP transactions generate competitive harm; (4) maintain cautious enforcement approaches that balance private and public interests. These recommendations aim to enhance antitrust effectiveness in promoting fair competition and innovation while contributing to a more equitable international patent system.